Estudo do fenômeno de barreira capilar: modelagem numérica e experimentação física - Paulo Augusto Diniz Silva (2011)
The purpose of this work is to study the phenomenon of capillary barrier from physical and numerical modeling. This phenomenon arises when a flow of water tries to pass through a geological arrangement consisting of at least a layer of fine textured material placed over a layer of coarse textured material that, in unsaturated conditions, prevents or restricts the entry of water in larger pores of the latter material. The physical experimentation used a physical model depicting a geological profile, with two horizontal layers, placed over of sandy soils with different textures, without grass, under the action of gravitational drainage, exposed to different weather infiltration. In its turn, the numerical simulation was done using a mathematical model based on finite volume method, using central differences for spatial derivatives and a fully implicit scheme for approximation of time derivatives, in which Richards equation and the van Genuchten model were employed.Without taking into account the phenomenon of hysteresis. Two scenarios were developed to investigate the phenomenon of capillary barrier. The first scenario concerns the simulation of infiltration during a total period of 4 hours, when, in particular, the emergence and magnitude of the capillary barrier and hydraulic behavior and the influence of the interface between two layers of soil were discussed. In the secondscenario, the same event was handled, however, over 10 hours with three alternate stages of precipitation in order to assess the recovery of the barrier and verify the performance of the numerical model in relation to the cyclic events of infiltration. Results showed clearly that the phenomenon of capillary barrier occurs due to the difference in hydraulic conductivity between the groups concerned. The magnitude of the capillary barrier the ability of the arrangement to restrict the flow of water into the lower layer is approximately 20% of the volume of water stored. Its recovery, that is, the arrangement, returns to work with a hydraulic bulkhead, when the difference between the hydraulic conductivities of the materials involved displays at least two orders of magnitude. Currently this phenomenon is thoroughly investigated because its application in the final cover of deposits of urban and industrial waste shows that it is an attractive alternative to restrict the phenomenon of infiltration in a built geological environment. Seeking to achieve the proposed objective, the work was done strategically in three directions. The first direction is dedicated to defining the physical and hydraulic models to develop thehydraulic models of the materials involved. The second direction is committed to develop a laboratory prototype, reduced physical model, to evaluate the most relevant aspects of the phenomenology and serve as a reference to the computational model. And the last direction aims to develop a computer code to investigate the hydraulic behavior of the arrangement, representing a capillary and complementary barrier to the analysis and i nterpretation of the phenomenon of capillary barrier